Mengintegrasikan Teknologi dalam Perencanaan Pembelajaran : Meningkatkan Minat dan Prestasi Hasil Belajar - Indri Purnama Putri Harefa; Sumiati Titi; Liena Hulu; Lisna Novalia (Institut Nalanda, 2024)
In the rapidly evolving digital era, technology has significantly transformed the way we learn and teach, especially in the context of primary education. Technology-based education integrates information and communication technology (ICT) into the learning process, utilizing tools such as computers, the internet, mobile devices, and educational software that are increasingly accessible. The use of this technology not only replaces traditional learning aids but also creates opportunities for more innovative, interactive, and efficient teaching methods. Technology-based learning can enhance students' interest and achievement while developing essential digital skills for the current era. Additionally, the application of technology enables the creation of a more collaborative and in-depth learning environment, providing access to various learning resources and encouraging students to be more actively involved in the learning process. While traditional learning in primary schools is often limited to less interactive methods, the integration of technology can increase student engagement, improve their interest in learning, and ultimately enhance their academic achievement. This article aims to explore how technology can be integrated into lesson planning in primary education to improve students' interest and performance.